Project-based learning. Experiences from the initial stage of implementation in a higher education institution. (1st January 2014) - Spalek, Seweryn
Project or problem-based learning (PBL) has been recognised as a teaching method. Due to its major aspect of the highly practical implementation of knowledge in order to achieve a final product at the end of the course, it is very often applied in non-academic courses. However, the issue of PBL's implementation at higher education institutions is of a more complicated nature. Under those circumstances, the challenges are of a different nature. In this paper, experiences from the first stage of implementation of PBL at a traditional teaching university are presented and discussed. The implications for further steps are drawn as well.